Effect of physical activity promotion program on adherence to physical exercise among patients with type II diabetes in North Shoa Zone Amhara region: a quasi-experimental study - Akine Eshete; Sadat Mohammed; Sisay Shine; Yosef Eshetie; Yibeltal Assefa; Nigussie Tadesse (BMC, 2023)
Abstract Background Diabetes is a significant global public health issue that necessitates self-management. However, this is difficult to put into practice and requires a new approach. The purpose of this study was to assess the effects of a physical activity promotion program on adherence to recommended physical activity and lessons to improve self-management. Methods A quasi-experimental study was conducted from January 2020 to February 2021 at North Shoa Zone Public Hospital. The study enrolled 216 type II diabetic patients from four public hospitals. Data were entered into Epi Data V.3.1 and analyzed using SPSS version 22. Data were presented as means of standard deviations for continuous variables and percentages for categorical variables. Intervention and control groups were compared before and after intervention using independent t-tests. A p-value less than 0.05 was considered significant for all statistical tests. Results A total of 216 type II diabetics participated in this study. Physical activity promotion programs increased adherence to the recommended number of days and duration (spending time) of physical activity (p < 0.0001). Participants who engaged in the physical activity promotion program significantly increased the mean scores for exercising moderate-intensity activities and spending time (p < 0.05), walking for at least 10 min continuously and spending time (p < 0.05), exercising moderate-intensity recreational activities and spending time (p < 0.05).There was a significant reduction in mean fasting blood glucose after participating in a physical activity program (p < 0.05). Conclusion This study demonstrates that a physical activity promotion program makes a significant difference in patient compliance with recommended physical activity and effectively improves patient glycemic control. Health care providers should integrate physical activity programs into existing systems as a common therapeutic service. Primary care platforms such as health posts and health centers can play a key role in integrating health promotion programs to improve self-management behaviors.